Propuesta técnica de una herramienta de comparación de métodos de embalaje por ocupación y costo para el sector farmacéutico en Colombia (2023)
Throughout the document, an analysis of the environmental problems generated by the pharmaceutical sector was carried out, specifically in the process of distribution and conservation of refrigerated cargo, where single-use containers are used that generate waste throughout the chain. of supply. The technical proposal forms a tool whose purpose is to increase the efficiency in the allocation of packaging for refrigerated products in use and cost, as well as to reduce the percentage of use of single-use inputs for Cold Chain distribution in the pharmaceutical sector of Colombia, through a strategy of allocation by discarding of conservation containers.